Algorithm for Assessing the Characteristics of a Waveguide Slot Antenna Array when Changing Antenna Element Phasing - A. F. Kryachko; N. A. Gladky; M. R. Bibarsov; B. A. Ayukov (Известия высших учебных заведений России: Радиоэлектроника, 2024)
Introduction. When operating antennas in various radio-electronic systems, the influence of phase shifter (PS) failures on the characteristics of phased array antennas, waveguide-slot phased array antennas (WSPAA) in particular, should be taken into account. A review of publications shows a lack of research studies into failures of these elements.Aim. Research of WSPAA characteristics in the event of PS failures, when their phase takes a value equal to zero instead of the required value.Materials and methods. Statistical modeling methods were used to study the impact of PS failures on WSPAA characteristics. Calculations were carried out using a PC and the Mathcad 15 applied mathematics package.Results. An algorithm for statistical modeling of the impact of PS failures on WSPAA characteristics is proposed. A relationship that connects the radiation pattern with the statistical sample volume and the number of failed PSs is presented. Malfunctions of emitters from 5 to 35 out of 50 elements were investigated. Changes in the following characteristics were obtained: standard deviation - from 0.064 to 0.18; relative values: radiation pattern width - from 8 to 18 %; level of side lobes - from 13 to 59 %; radiation power - from 0.9 to 0.3.Conclusion. The results obtained can be generalized and used in radio-electronic systems with antenna arrays at the stage of their development. Future work will address the influence of PS failures with phases being established randomly and with random values, as well as PS failures in which power does not pass into the emitter. Another important area concerns compensation of distortions resulting from failures of antenna elements.